Pengaruh Literasi Digital terhadap Motivasi Belajar dan Adaptabilitas Karier pada Mahasiswa Manajemen di Jakarta - Handoko Wahyu Pamungkas (NAJAHA, 2026)
This study aims to examine the effect of digital literacy on learning motivation and career adaptability among final-year management students. Grounded in Career Construction Theory (CCT), the study employs a cross-sectional quantitative design with a survey of 250 students at a private university in Jakarta. Data were analyzed using simple linear regression for each hypothesis. Results confirm: (H1) digital literacy positively and significantly affects career adaptability (β = 0.623; R² = 0.739; F(1,248) = 701.570; p < .001); (H2) digital literacy positively and significantly affects learning motivation (β = 0.557; R² = 0.559; F(1,248) = 314.785; p < .001); and (H3) learning motivation positively and significantly affects career adaptability (β = 0.840; R² = 0.744; F(1,248) = 720.068; p < .001). All three hypotheses are statistically supported. These findings imply the importance of integrating digital literacy development into university curricula as a foundation for nurturing learning motivation and career adaptability in the digital era. Keywords: digital literacy, career adaptability, learning motivation, linear regression, Career Construction Theory